What Principles in What Proceedings? The Use and Development of General Principles of Law in the ICJ’s Advisory vs Contentious Jurisprudence - Dordeska, Marija (Polish Review of International and European Law, 2026)
This article examines how the International Court of Justice and its predecessor, the Permanent Court of International Justice, identified and developed general principles – the third source of international law codified in Article 38(1)(c) of the ICJ Statute – across advisory and contentious proceedings. Drawing on a database of 164 principles identified between 1922 and 2025, it compares their formulation, function, and evolution in both contexts. The study challenges the assumption that general principles in advisory proceedings are inherently more abstract or foundational. While contentious cases dominate in identifying and refining general principles, advisory opinions contribute proportionately to their development, particularly when the opinion is adversarial in nature.